2018
DOI: 10.1016/s2352-4642(18)30274-8
|View full text |Cite
|
Sign up to set email alerts
|

Chest radiographs versus CT for the detection of rib fractures in children (DRIFT): a diagnostic accuracy observational study

Abstract: SummaryBackgroundInternationally, chest radiography is the standard investigation for identifying rib fractures in suspected physical abuse in infants. Several small observation studies in children have found that chest CT can provide greater accuracy than radiography for fracture detection, potentially aiding medicolegal proceedings in abuse cases; however, to our knowledge, this greater accuracy has not been comprehensively evaluated. We aimed to determine differences in rib fracture detection rates between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 27 publications
(41 reference statements)
0
28
0
Order By: Relevance
“…Studies show that CT imaging is more sensitive than radiography for detecting rib fractures in pediatric cases (Gorincour et al, 2015; Hong et al, 2011; Shelmerdine et al, 2018; Wootton‐Gorges et al, 2008) and more sensitive than autopsy for detecting fractures in general (Krentz et al, 2016; Sieswerda‐Hoogendoorn, Soerdjbalie‐Maikoe, de Bakker, & van Rijn, 2014; van Wijk et al, 2017). Using the number and location of rib fractures identified at autopsy as the gold standard, Shelmerdine et al (2018) were able to correctly identify three times as many rib fractures using PMCT imaging than radiography and the accuracy was greater regardless of fracture location or the radiologists' experience. Similarly, Wootton‐Gorges et al (2008) and Hong et al (2011) reported that PMCT was more sensitive than radiography for detecting rib fractures.…”
Section: Methods and Techniques Available To The Forensic Anthropologistmentioning
confidence: 99%
“…Studies show that CT imaging is more sensitive than radiography for detecting rib fractures in pediatric cases (Gorincour et al, 2015; Hong et al, 2011; Shelmerdine et al, 2018; Wootton‐Gorges et al, 2008) and more sensitive than autopsy for detecting fractures in general (Krentz et al, 2016; Sieswerda‐Hoogendoorn, Soerdjbalie‐Maikoe, de Bakker, & van Rijn, 2014; van Wijk et al, 2017). Using the number and location of rib fractures identified at autopsy as the gold standard, Shelmerdine et al (2018) were able to correctly identify three times as many rib fractures using PMCT imaging than radiography and the accuracy was greater regardless of fracture location or the radiologists' experience. Similarly, Wootton‐Gorges et al (2008) and Hong et al (2011) reported that PMCT was more sensitive than radiography for detecting rib fractures.…”
Section: Methods and Techniques Available To The Forensic Anthropologistmentioning
confidence: 99%
“…2 and 3). CT has been shown to be more sensitive than radiographs for assessing rib fractures [19,47,48], although radiographs might be more sensitive for phalangeal fractures [19] and metaphyseal corner fractures (classic metaphyseal lesions); more study is needed comparing CT to radiography in this setting [13]. In the absence of signs of trauma, however, finding the cause of death is more challenging because expected postmortem changes and antemortem lung and brain pathology can have a similar appearance on postmortem CT [20,34,35,43,49].…”
Section: Clinical Applications Of Postmortem Ctmentioning
confidence: 99%
“…Postmortem CT is superior to autopsy in detection of fractures [33], but evidence is limited that it is superior to radiographs in the setting of skeletal dysplasia [8,12,27]. Postmortem CT has been found to be better than radiography for rib fractures [47,48]; however CT has been found to be more limited in the setting of natural death [33,50,52]. But when no cause of death is found by autopsy, concordance with CT has been shown to be very good [34,51].…”
Section: Challengesmentioning
confidence: 99%
“…The idea that certain lesions are likely to represent abuse is widely believed but is based on circular reasoning (Berthold et al, 2018;Chauvin-Klimoff, Allard-Dansereau, & Colbourne, 2018;Flaherty et al, 2014;Högberg, Andersson, Högberg, & Thiblin, 2019;Paine, Fakeye, Christian, & Wood, 2019). Indeed, much current research is directed at maximizing the evidence of abuse (Raynor, Konala, & Freemont, 2018;Shelmerdine et al, 2018;Wood et al, 2018).…”
Section: Broken Bones and Irresponsible Testimony?mentioning
confidence: 99%